Feasibility and safety of extended‐release naltrexone treatment of opioid and alcohol use disorder in HIV clinics: a pilot/feasibility randomized trial. (8th February 2017) - Korthuis, Philip T.; Lum, Paula J.; Vergara‐Rodriguez, Pamela; Ahamad, Keith; Wood, Evan; Kunkel, Lynn E.; Oden, Neal L.; Lindblad, Robert; Sorensen, James L.; Arenas, Virgilio; Ha, Doan; Mandler, Raul N.; et al.
Abstract: Background and aims: HIV‐infected people with substance use disorders are least likely to benefit from advances in HIV treatment. Integration of extended‐release naltrexone (XR‐NTX) into HIV clinics may increase engagement in the HIV care continuum by decreasing substance use. We aimed to compare (1) XR‐NTX treatment initiation, (2) retention and (3) safety of XR‐NTX versus treatment as usual (TAU) for treating opioid use disorder (OUD) and/or alcohol use disorder (AUD) in HIV clinics. Design: Non‐blinded randomized trial of XR‐NTX versus pharmacotherapy TAU. Setting: HIV primary care clinics in Vancouver, BC, Canada and Chicago, IL, USA. Participants: Fifty‐one HIV‐infected patients seeking treatment for OUD ( n = 16), AUD ( n = 27) or both OUD and AUD ( n = 8). Measurements: Primary outcomes were XR‐NTX initiation (receipt of first injection within 4 weeks of randomization) and retention at 16 weeks. Secondary outcomes generated point estimates for change in substance use, HIV viral suppression [HIV RNA polymerase chain reaction (pcr) < 200 copies/ml] and safety. Findings: Two‐thirds (68%) of participants assigned to XR‐NTX initiated treatment, and 88% of these were retained on XR‐NTX at 16 weeks. In comparison, 96% of TAU participants initiated treatment, but only 50% were retained on medication at 16 weeks. Mean days of opioid use in past 30 days decreased from 17.3 to 4.1 for TAU and from 20.3 to 7.7 for XR‐NTX. Mean heavy drinking days decreased from 15.6 to 5.7 for TAU and 12.5 to 2.8 for XR‐NTX. Among those with OUD, HIV suppression improved from 67 to 80% for XR‐NTX and 58 to 75% for TAU. XR‐NTX was well tolerated, with no precipitated withdrawals and one serious injection‐site reaction. Conclusions: Extended‐release naltrexone (XR‐NTX) is feasible and safe for treatment of opioid use disorder and alcohol use disorder in HIV clinics. Treatment initiation appears to be lower and retention greater for XR‐NTX compared with treatment as usual (clinicaltrials.gov NCT01908062).